Towards understanding thermal history of the Universe through direct and indirect detection of dark matter. Issue 10 (3rd October 2017) - Roszkowski, Leszek; Trojanowski, Sebastian; Turzyński, Krzysztof
Abstract: We examine the question to what extent prospective detection of dark matter by direct and indirect- detection experiments could shed light on what fraction of dark matter was generated thermally via the freeze-out process in the early Universe. By simulating putative signals that could be seen in the near future and using them to reconstruct WIMP dark matter properties, we show that, in a model- independent approach this could only be achieved in a thin sliver of the parameter space. However, with additional theoretical input the hypothesis about the thermal freeze-out as the dominant mechanism for generating dark matter can potentially be verified. We illustrate this with two examples: an effective field theory of dark matter with a vector messenger and a higgsino or wino dark matter within the MSSM.